Variations V: "Escaping Stagnation" Through Movement of Signification - Hoover, Elizabeth (Current Musicology, 2010)
Variations V, a collaborative event by the Merce Cunningham Dance Company and composer John Cage, premiered on July 23,1965 at Lincoln Center for the Performing Arts as part of the New York Philharmonic's French-American Festival. Following Edgard Varese's Hyperprism, Pierre Boulez's Improvisation sur Mallarme II, and Elliot Carter's Second String Quartet, Variations V contrasted greatly in composition and media with the pieces of the first half of the Philharmonic's program. Instead of orchestral instrumentalists performing live on their trumpets, cellos, and violins, recorded and radio sounds filled the concert hall through six speakers "distributed around Philharmonic Hall" (Hughes "Leaps" 1965:10); the choreographed movements of seven dancers occupied the stage; and filmed images projected on a screen behind them. The performance was an over-whelming multimedia display, with no immediate connection between the various modes of artistic expression.